Collaborative Governance dalam Penanganan Covid-19 di Kabupaten Poso - Karmila Akib; Muhammad Yaser Fedayyen; Sapruni Sapruni (Kolaborasi : Jurnal Administrasi Publik, 2023)
This study aims to determine the collaboration process between stakeholders in handling Covid-19 in Poso District and the obstacles faced. The method used in this research is a qualitative method with data collection techniques through observation and interviews and analysis is carried out starting from reduction, data presentation and verification and conclusion drawing. The results of the study explain that the handling of Covid-19 in Poso Regency can run well because the Poso Regency Regional Government applies the concept of Collaborative Governance. Although there are several obstacles in the collaboration process carried out, namely the shortage of health workers and funeral workers, limited budget for the purchase of personal protective equipment, medicines, oxygen, Covid-19 test kits, isolation costs for health workers and incentives for health workers and tracking personnel, the unavailability of Covid-19 test kits, low public awareness of the dangers of Covid-19 and low public participation in vaccination activities.